A noção da cura em Bion : do desvelamento do inconsciente à expansão mental - Lima, Edilene de (2012)
The conception of cure in psychoanalytic treatment is controversial and it presents itself as a difficult topic to discuss. The way it is understood by the traditional medical model, this idea is not appropriated to evaluate the results of the treatment process and to measure the patient?s changes. This work intends to analyze the notion in discussion and the psychoanalytic process concept as well in selected texts of Wilfred Ruprecht Bion (1897-1979) works. Looking forward to present the author's work, the texts surveyed have been divided in three periods: groupal, focus on psychosis and epistemological. In each chapter, it is exposed the concepts developed by Bion in each period and then the notion of cure that could be explicated in each one of them. Along the author's works, it was observed that the conception of cure has been modified and extended in each period. During the groupal phase, this idea is related to assist the patient to become conscious the unconscious parts which would achieve primitive fantasies. In focus on psychosis period, prevails the conception of cure associated to the patient's symptoms progress and the increase of the capacity related to the development of thought, to modulate the splitting mechanisms and the projective identification. Finally, in the epistemological phase, Bion strengths the idea of growth as mental expansion which gathers in its operation the being and the knowing.